Re-imagining church through autism: a Singaporean case study - van Ommen, Armand Léon (Practical theology, 2022)
Theological reflection on autism is a fairly recent development, although several practical resources for churches seeking to be inclusive of autistic people have been published since 2011. Even so, the emerging discussion lacks concrete examples and analyses of churches that practice inclusion and belonging. This article fills this gap by describing and analysing a church in Singapore, the Chapel of Christ our Hope, where autistic people are central. Themes that were identified in the fieldwork with this church were their ecclesiology (including a theology of belonging that strongly influences all this church does), the way autism reveals the meaning of liturgy, autistic participation, caring for differing needs, and different views of autism. The case study is not meant as a blueprint for churches to follow, but offers practical-theological insights for churches that want to create places of belonging for autistic and non-autistic people alike.